The Diversity of pollinator insects in vegetable gardens, Kabawo District, Muna Regency - Fitriani, Wa Ode; Kilowasid, Laode Muhammad Harjoni; Arma, Makmur Jaya; Pakki, Terry; Hadini, Hamirul (Anjoro: International Journal of Agriculture and Business, 2024)
Pollinator insects play an important role in pollination to increase the productivity of flowering plants. The aim of this study was to analyze the abundance, diversity, and specific taxon of insect pollinators among different vegetable crops in local farmers' gardens. Insects were sampled from four gardens, namely polyculture long bean (KKP), eggplant polyculture (KT), curly chili monoculture (KCK), and Indofood chili monoculture (KCI) used nets and light traps. The results showed that the abundance and diversity of pollinator insects varied between gardens. The pollinator insect community in KCI was most similar to that in KCK; KT was similar to the KCI and KCK groups, while KKP were separate from the KT, KCK and KCI groups. The richest genus occurs in KKP, while chili plantations are the poorest. The apis genus in KKP and KT, and the Nomina genus in KCK and KCI were dominant. The specific pollinator insect genus in KKP is the richest. It concluded that plant species and cropping patterns contribute to the composition and diversity of the pollinator insect community.